SUICIDAL BEHAVIOR IN LIVER CIRRHOSIS PATIENTS - Ergasheva Yu.Y (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Relevance    The  study  was  conducted  in  42  patients  with  cirrhosis  of  the  liver  with established disability, the features of suicidal thoughts and attempts in this category of patients were studied. Chronic liver disease is a long-term and debilitating condition in which comorbid mental illnesses are added to the incidence. The present study is aimed at studying how cirrhosis of the liver affects the overall picture of suicide. It remains unclear how physical disability can lead to an increased risk of suicidal acts.